The Relationship Between Stress Levels and Health-Seeking Behavior in Hemodialysis Patients - Sri Winarni; Yustina Kristianingsih; Ignata Yuliati (Faculty of Health Sciences, Universitas Muhammadiyah Surabaya, East Java, Indonesia, 2025)
Background: Kidney dysfunction causes disruptions in the body, necessitating long-term treatment to replace the kidneys' role and function. This can lead to lifelong dependence on dialysis machines. These changes in patients can trigger stress, such as withdrawing from others and suicidal thoughts. The purpose of this study was to analyze the relationship between stress levels and health-seeking behavior. Methods: This study used a correlational design with a cross-sectional approach. The population used was hemodialysis patients at a hospital in Mojokerto City, meeting the inclusion criteria. Respondents in this study were 83 hemodialysis patients selected using a purposive sampling technique. Data collection was carried out using the DASS questionnaire and the Health-Seeking Behavior Questionnaire. The collected data were analyzed using the Rank Sperman statistical test. Results: The results of the study concluded that respondents experienced moderate stress levels of 49.2%, mild stress of 38.1%, and severe stress of 12.7%. The behavior of seeking health assistance for CKD patients undergoing hemodialysis was 26% going to the hospital, 225 going to the doctor/clinic, 21% going to the community health center, 17% taking medication purchased at the pharmacy, 4% taking medication purchased at the shop, 4% taking herbal medicine/medicine, 4% resting/sleeping and 2% just left alone. There is a weak negative relationship where the lighter the stress level, the better the behavior of seeking health assistance Conclusion: There is a weak negative correlation, where lower stress levels lead to better health-seeking behavior. It is hoped that the management of Mojokerto City Hospital can plan or develop a program to reduce stress levels for patients and their families by providing health education about CKD and appropriate health-seeking behavior to prevent complications